The role of Jadidism ideas in New Uzbekistan. - Neʼmatova Sarvinozxon Nizomjon qizi. (Zien Journals, 2024)
This article discusses the ideas of jadidism and the development of a harmonious personality. Jump to navigation In modern times, the ideas of jadidism play a great role in the upbringing of spiritually mature and harmonious generation, the development of education and upbringing, the building of an enlightened society
Keywords: Upbringing; enlightenment; self-awareness